Development of an Adventure Game to Enhance Mathematics Learning for Grade 6 Students - ชื่นชม อนันต์พล; โพธิ์เกษม ภนิดา; พิมพาภรณ์ ณัฐชฎา; รชตวัฒนกุล รัชเมธี (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This study employed a pre-experimental research design, specifically a one-group pretest–posttest design. The objectives were: (1) to develop an adventure-based game to enhance mathematics learning for Grade 6 students, and (2) to compare students’ mathematics learning achievement before and after learning through the developed game. The population consisted of 53 Grade 6 students from Wat Phonmanee School, and the sample group included 30 students selected through purposive sampling. The experiment was conducted from May to September 2024. The research instruments included: (1) an adventure-based game developed based on the Software Development Life Cycle (SDLC), and (2) a mathematics learning achievement test validated by experts. The statistical methods used for data analysis were mean, standard deviation, and the dependent t-test. The results revealed that the students’ posttest scores (x̄= 22.47, S.D. = 2.74) were significantly higher than their pretest scores (x̄= 14.90, S.D. = 2.51) at the .05 level of significance. Furthermore, the developed adventure-based game had an Effectiveness Index (E.I.) of 0.50, indicating that the students’ learning progress increased by 50 percent, which met the established criteria.